Aktywizacja kobiet dojrzałych na lubuskim rynku pracy: mit czy rzeczywistość? = Activation of mature women in the labour market of Lubuskie region: a myth or reality? - Trzop, Beata; Witkiewicz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the presence of mature women in the labour market of Lubuskie region. The category studied in this paper are women over 50. This age categorization of the respondents is closely linked to the processes that locate the respondents between late middle adulthood and late adulthood. The most important factors which should be pointed out is the decline or end of their professional activity. Apart from numerous social roles of mature women (mothers of adult children, grandmothers, wives/partners, daughters - carers) we focus on mature women as mature employees.
Keywords: starzenie się społeczeństwa; cykle życia; dyskryminacja dojrzałych kobiet na rynku pracy; ageing societies; life cycles; discrimination against mature women in the labour market